2003
DOI: 10.1177/0021998303034505
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Mixed-Mode Progressive Delamination in Composite Materials

Abstract: A new decohesion element with the capability of dealing with crack propagation under mixed-mode loading is proposed and demonstrated. The element is used at the interface between solid finite elements to model the initiation and non-self-similar growth of delaminations in composite materials. A single relative displacement-based damage parameter is applied in a softening law to track the damage state of the interface and to prevent the restoration of the cohesive state during unloading. The softening law is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
857
2
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,410 publications
(875 citation statements)
references
References 43 publications
9
857
2
7
Order By: Relevance
“…The surfaces obtained by the different criterion are represented in Figure 6. The values predicted by the new criterion are very close to Ye's criterion, that has been successfully used in previous investigations [24].…”
Section: Initial Damage Surfacesupporting
confidence: 81%
See 4 more Smart Citations
“…The surfaces obtained by the different criterion are represented in Figure 6. The values predicted by the new criterion are very close to Ye's criterion, that has been successfully used in previous investigations [24].…”
Section: Initial Damage Surfacesupporting
confidence: 81%
“…However, Camanho et al [24] have shown that the expression proposed by Benzeggagh and Kenane [36] for the critical energy release rate for a mixedmode ratio is more accurate for epoxy and PEEK composites. The expression proposed by Benzeggagh and Kenane for the critical energy release rate G c is:…”
Section: Propagation Criterionmentioning
confidence: 99%
See 3 more Smart Citations